2008
DOI: 10.4103/0255-0857.43582
|View full text |Cite
|
Sign up to set email alerts
|

Status of high level aminoglycoside resistantEnterococcus faeciumandEnterococcus faecalisin a rural hospital of central India

Abstract: Considering the emergence of high level aminoglycoside resistance (HLAR) in enterococci this study was undertaken to determine their status in a rural setting. HLAR by disc diffusion and agar dilution, beta lactamase by nitrocefin disc and vancomycin resistance by agar dilution was determined in 150 enterococcal isolates, as per NCCLS guidelines. Only two species, Enterococcus faecalis (85.5%) and Enterococcus faecium (14.7%) were recovered, mostly from blood. Forty six percent showed HLAR. Multi drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
38
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 9 publications
19
38
3
Order By: Relevance
“…According to the results of the present study the prevalence of E. faecalis among infectious clinical samples was about 2 fold higher than E. faecium, similar results have been reported from other studies in Iran (Jabalameli et al, 2009;Sharifi et al, 2013), Malaysia (Sharifi et al, 2013), central and south India (Bhat, Paul, & Ananthakrishna, 1998;Fernandes & Dhanashree, 2013;Mendiratta et al, 2008); while in some other studies the prevalence of E. faecium has been reported higher than E. faecalis (Kapoor, Randhawa, & Deb, 2005). Fernandes and Dhanashree (2013) suggested that possessing the hemolysin and gelatinase might be the reason of higher prevalence of E. faecalis in infectious samples (Fernandes & Dhanashree, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of the present study the prevalence of E. faecalis among infectious clinical samples was about 2 fold higher than E. faecium, similar results have been reported from other studies in Iran (Jabalameli et al, 2009;Sharifi et al, 2013), Malaysia (Sharifi et al, 2013), central and south India (Bhat, Paul, & Ananthakrishna, 1998;Fernandes & Dhanashree, 2013;Mendiratta et al, 2008); while in some other studies the prevalence of E. faecium has been reported higher than E. faecalis (Kapoor, Randhawa, & Deb, 2005). Fernandes and Dhanashree (2013) suggested that possessing the hemolysin and gelatinase might be the reason of higher prevalence of E. faecalis in infectious samples (Fernandes & Dhanashree, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Two other studies from Bangladesh reported isolation rates of E. faecalis as 62.5% by Islam and 71.18% by Akhter [14] that were almost similar to our present study [1,14]. The isolation rate of Enterococcus Faecalis from India by Mendiratta et al [15] (85.3%) and Jada & Jayakumar et al…”
Section: Discussionsupporting
confidence: 88%
“…[5] (100%) from Kancheepuram were higher than our present study [5,15]. Reasons could be the predominance of E. fecalis in the endogenous flora of the body [16].…”
Section: Discussioncontrasting
confidence: 62%
“…Similar result was also observed by Mendiratta et al,2008. High HLGR in E.faecalis and HLSR in E.faecium observed has also been reported (Bhat et al, 1997, Agarwal et al,1999 as also vice versa (Karmarkar et al, 2004).…”
Section: IVsupporting
confidence: 86%